Waterer equipment - Tóth, László (Animal welfare, Ethology and Housing Systems (AWETH), 2007)
The basic properties of the watering (drinking) devices used in livestock farms are shown in the frame of this brief review – laying special emphasis on the advantages and disadvantages of the different designs, the animal needs, taking the relations to the environment and the behaviour of the species into consideration as well.We draw the attention of those interested in this field to what an important role these relatively simple constructions play in the alimentation and the comfort feeling of the animals.
Keywords: drinking water; self-waterers; cattle; pig; poultry